THE EFFECT OF LOW TEMPERATURES ON ENZYME SYSTEM OF THE CELLS OF THE FRUIT AND VEGETABLE RAW MATERIALS - Nicholay G. Scheglov (Современная наука и инновации, 2022)
The article discusses one of the key issues that affect the duration of storage of fruit and vegetable raw materials - the choice of a temperature mode of storage, confirmed the experimental data taking into account the changes of the thermophysical properties of raw materials at the interface of the phases, liquid or gas and confrontation of the cell as a living system temperature drop.